1978
DOI: 10.1177/003754977803000602
|View full text |Cite
|
Sign up to set email alerts
|

MEDECS, a simulator for mediterranean ecosystems

Abstract: MEDECS, the mediterranean ecosystem simulator, was developed to model the dynamics of mediterranean- type vegetation in southern California and central Chile. MEDECS is a difference/differential-equation model which simulates the seasonal patterns of resource use and plant response in one-day time steps. It uses submodels of plant growth, decompo sition, and inorganic nutrient release to describe the effects of physiological processes, nutrient availability, and environmental parameters. MEDECS is a compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1983
1983
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…Since the pioneer simulation exercises with biogeochemical models of Eckardt et al (1975) and Miller et al (1978) carried out in Mediterranean‐type ecosystems, most models derive canopy performance from that of the leaf. Among these, Sellers et al (1992) provide a good conceptual framework and has the merit of breaking the procedure down into stages.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneer simulation exercises with biogeochemical models of Eckardt et al (1975) and Miller et al (1978) carried out in Mediterranean‐type ecosystems, most models derive canopy performance from that of the leaf. Among these, Sellers et al (1992) provide a good conceptual framework and has the merit of breaking the procedure down into stages.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the solid and dashed lines of a species represent the effects of competition on the species. (Miller et al 1978) 3.6 Future Research Needs A definitive answer to the question of the role of biodiversity and ecosystem function requires experimental work specifically designed to address this question. Presently one such study is underway with the annual grassland ecosystem at Jasper Ridge (N. Chiariello, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, their models are an important avenue for exploring the question of biodiversity and ecosystem function. Using different combinations of two species, Adenostoma Jasciculatum and Arctostaphylos glauca, Miller et al (1978) showed that mixed communities had greater net photosynthetic production than monotypic communities (Fig. 3.20A).…”
Section: Energy Capture Resource Use and Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Κατηγορίες μπορούν να δημιουργηθούν βάσει του εμπειρισμού ή του οικοφυσιολογικού ντετερμινισμού που διαθέτουν. Οι προσεγγίσεις που έχουν χρησιμοποιηθεί ποικίλουν από πιθανοθεωρητικές (Horn 1976, Noble andSlatyer 1980) έως καθαρά μηχανιστικές που εστιάζουν άλλοτε στη δυναμική της βλάστησης ) και άλλοτε στην οικοφυσιολογία των ειδών που την συγκροτούν (Miller et al 1978). Τα μοντέλα βλάστησης που εστιάζουν σε δασικά οικοσυστήματα παρουσιάζουν ιδιαίτερο ενδιαφέρον για τρεις κυρίως λόγους: 1) τη διαχειριστική σημασία της πρόγνωσης της δομής, οικονομικά εκμεταλλεύσιμων δασικών συστημάτων, 2) τη μακροβιότητα των δασικών οικοσυστημάτων (συνήθως μεγαλύτερη από το μέσο όρο ζωής ενός ερευνητή), η οποία δεν επιτρέπει τη διεξαγωγή πειραμάτων που θα κάλυπταν το συνολικό εύρος της εξέλιξής τους και 3) τον ιδιάζοντα ρόλο που καλούνται να διαδραματίσουν τα συγκεκριμένα οικοσυστήματα όσον αφορά στην αλληλεπίδρασή τους με το κλιματικό σύστημα (δέσμευση CO2 -φαινόμενο θερμοκηπίου -πρωτόκολλο Kyoto).…”
Section: μηχανιστικά μοντέλα προσομοίωσης της δυναμικής της βλάστησης σε τοπική κλίμακαunclassified